Geowizualne bazy danych a reprodukowanie psychosocjologicznych mitów poznawczych - Luczys, Piotr (Człowiek i Społeczeństwo, 2013)
The development of geographic information accompanied by the expansion towards accumulation of the greater and greater amount of geospatial data – initiated the specific theoretical marriage of reflection on objectivizing character of the digital imago mundi and the cognitive relationship between the “state of the world” and the “state of the mind”. Whereby, electronic repositories of “geoevery- kind” data constitute the direct articulation of consciously acquiring and organising spatial data, additionally supported by the evidence of emergence of the new and inspired by “the sciences of cognition” (that is: cognitive psychology, cognitive science, philosophy of the mind, etc.) technological solutions in this realm. Such a theoretically-technical amalgam of information considerably limits – and being the clue of this paper – the explanatory usefulness of digital spatial data in the sociological analysis and deforms the contemporary state of knowledge regarding spatially-driven collective behaviours, leading to the rise of the mentioned myths.